A Correlation Between Knowledge And Socio-Economics With The Selection Of Contraceptives In Coastal Areas In The Working Area Of Luas Health Center Of Kaur Regency - Yeka Hermalena; Fikitri Marya Sari; Darmawansyah Darmawansyah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: Family planning programs are direct efforts aimed at reducing birth rates through the use of contraceptives. The success of family planning programs in Indonesia is influenced by several factors, including socioeconomic status, culture, education, religion, and women's status. The purpose of this study was to determine the relationship between knowledge and socioeconomic status and contraceptive choice in the working area of ​​Luas Health Center in Kaur Regency.. Method: The method used was an analytical survey with a cross-sectional design. Primary data were collected by distributing questionnaires to 95 couples of childbearing age in Luas Health Center in Kaur Regency using a simple random sampling technique. Result and Discussion: Data analysis was performed using the Chi-Square test. Univariate analysis results showed that almost half (42.1%) of fertile couples had insufficient knowledge, more than half (55.8%) of fertile couples with incomes below Rp 2,670,039, and more than half (61.1%) of fertile couples used hormonal contraceptives. Bivariate analysis results showed a correlation between knowledge and contraceptive choice (p=0.000) and socioeconomic status (p=0.029). Conclusion: The researchers recommend that health centers) provide education and support to the community to help them understand the benefits and impacts of hormonal and non-hormonal contraceptive use, enabling couples of childbearing age to use appropriate contraceptives.